KNOWLEDGE, ATTITUDE AND PRACTICES OF CRITICAL CARE NURSES REGARDING CARDIOPULMONARY RESUSCITATION AT TERTIARY CARE HOSPITAL PESHAWAR - Miss Nabila Naz; Mr Waleed Iqbal; Mr Rafiullah; Miss Basmin Bibi; Miss Roman Laila; Miss Sher Bano (International Journal of Contemporary Issues in Social Sciences, 2024)
Cardiopulmonary resuscitation (CPR) is a vital emergency technique, crucial for improving survival outcomes after cardiac arrest. High-quality CPR is essential, especially in critical care units where patients are at high risk. Nurses, often the first responders in these scenarios, must be proficient in CPR to enhance patient survival and quality of life. Proper CPR techniques are necessary to avoid serious complications, making proficiency critical in emergencies. This study evaluated the knowledge, attitudes, and practices (KAP) of critical care nurses regarding CPR at tertiary Care hospitals in Peshawar. A descriptive cross-sectional design was employed, with 169 structured questionnaires administered and analyzed using SPSS version 25.0. The study included responses from nurses at Lady Reading Hospital (LRH), Khyber Teaching Hospital (KTH), and Hayatabad Medical Complex (HMC). Results indicated that 78% of respondents had good knowledge of CPR, 76% demonstrated good CPR practices, but 48% had a negative attitude towards it. The data revealed a significant correlation between knowledge and the practice of CPR. The findings highlight that while most intensive care nurses possess excellent CPR knowledge and practices, their attitudes towards CPR need improvement. The study concludes that despite having expertise in critical care settings, nurses need more training in Basic Life Support (BLS). Hospitals should foster a culture that emphasizes the importance of CPR for better patient outcomes. Integrating simulation scenarios in CPR training can provide a safe environment for nurses to enhance their skills. This approach can address gaps in knowledge and attitudes, ultimately leading to improved CPR performance and patient survival rates. Overall, the study underscores the need for continuous education and supportive practices to ensure nurses are fully prepared to perform effective CPR, thus saving lives in critical situations.